Histological Study of the Digestive Tract of Liza abu (Heckel) 1-Esophagus - Hussain, Hanan R.D.; Abid, Wijdan B. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study includes histological structure of digestive tract of Liza abu , Anatomical results found that the digestive tract occupied the largest part of abdominal cavity , the mean gut length was (45.5) cm and relative gut length was (2.9) . esophagus was a muscular tube length (1.5) cm , esophagus wall containing longitudinal straight unbranched folds numbering (9) . Histological study results found that the esophagus composed of four tunica : mucosa , submucosa , muscularis and serosa . The results found that the mucosa consists of three layers : epithelium , lamina propria and muscularis mucosa . The epithelial layer was stratified squamous epithelium thickness (139.1) µ containing big size mucous cells strongly staining with PAS and AB .Lamina propria under epithelial tissue thickness(148.3) µ composed of irregular dense connective tissue and does not contain esophageal glands . Muscularis mucosa composed of smooth muscle fibers thickness(10) µ. Submucosa was irregular dense connective tissue enriched with blood capillaries thickness(30) µ . Tunica muscularis composed of bundles of stri ated skeletal muscle fibers thickness(220.5) µ arranged in two layers internal longitudinal layer thickness(73.5) µ and external circular layer thickness (147) µ . Serosa was thin layer of loose connective tissue thickness (21) µ .